Adrenal Myelolipomas Involved by Plasma Cell Myeloma. Issue 5 (20th July 2018) - Lin, Chieh-Yu; Levy, David; Higgins, John P T; Kunder, Christian A; Kao, Chia-Sui
Abstract: Objectives: To report the presence and evaluate the frequency of plasma cell neoplasms within adrenal myelolipomas. Methods: Adrenal myelolipomas within our institution were reviewed for the presence of hematologic neoplasia, and a review of the literature was performed. Results: Two (9%) of 23 adrenal myelolipomas were involved by plasma cell myeloma. The patients were 71 and 81 years old, one woman and one man, with tumors measuring 7 cm and 8.5 cm, respectively. Both tumors contained large aggregates of dysplastic plasma cells occupying at least one ×10 field and demonstrated light chain restriction. Neither had an established diagnosis of plasma cell neoplasm previously. After receiving therapy, one patient exhibited a stable clinical course 1 year after diagnosis while the other died of disease 3 years later. Conclusions: We report the first two cases of adrenal myelolipoma involved by plasma cell myeloma, a rare and subtle finding that has significant clinical implications.